2006
DOI: 10.1038/sj.jp.7211412
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypothermia via selective head cooling as neuroprotective therapy in term neonates with perinatal asphyxia: an experience from a single neonatal intensive care unit

et al.

Abstract: Objective: The objective of this study was to determine the efficacy of mild hypothermia via selective head cooling as a neuroprotective therapy in term infants with perinatal asphyxia.Study design: Full-term newborns who had 5 min Apgar scores <6, first arterial blood gas pH<7.10 or BD>15 mEq/l, and with the clinical signs of encephalopathy were enrolled within 6 h after birth. Patients were randomized to receive mild hypothermia treatment via selective head cooling for a total of 72 h or receive routine trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 24 publications
4
69
0
1
Order By: Relevance
“…Consensus on Science A large body of evidence from 3 large randomized studies (LOE 1 [132][133][134] ) and 2 small randomized trials (LOE 1 135,136 ) demonstrated that induced hypothermia (33.5°to 34.5°C) implemented within 6 hours of birth in term infants at highest risk for brain injury (as defined by specific protocols) and with further treatment in neonatal intensive care units is associated with significantly fewer deaths and less neurodevelopmental disability at 18-month follow-up. The number needed to treat is 9.…”
Section: Therapeutic Hypothermia Nrp-024a Nrp-024bmentioning
confidence: 99%
“…Consensus on Science A large body of evidence from 3 large randomized studies (LOE 1 [132][133][134] ) and 2 small randomized trials (LOE 1 135,136 ) demonstrated that induced hypothermia (33.5°to 34.5°C) implemented within 6 hours of birth in term infants at highest risk for brain injury (as defined by specific protocols) and with further treatment in neonatal intensive care units is associated with significantly fewer deaths and less neurodevelopmental disability at 18-month follow-up. The number needed to treat is 9.…”
Section: Therapeutic Hypothermia Nrp-024a Nrp-024bmentioning
confidence: 99%
“…Reduction in temperature is achieved by running 10°C water through a coil of tubing wrapped around the infant's scalp for 72 hours [91]. Other studies have showed improvement in short-term computed tomographic changes [92], neurodevelopment outcome at 18 months [5], or combined outcome of severe disability and death [93]. As with other surface cooling methods, some devices are adjusted manually or automatically via a feedback mechanism [93].…”
Section: Cool Caps For Infantsmentioning
confidence: 99%
“…1). There were two systematic reviews [90,91], and five randomized clinical trials (RCT) [92][93][94][95][96] showing increased chance of outcome without disabilities with mild hypothermia therapy. The relative risk (RR) for reduction of death or major neurodevelopmental disability varied between 1.35 and 2.43.…”
Section: Asphyxiamentioning
confidence: 99%